SALAT SUBUH DAN DIMENSI IDEAL MAHASISWA - Ahmad Yasser Mansyur; Sitti Syawaliyah Gismin (Program Studi Psikologi Islam, Fakultas Psikologi, Universitas Islam Negeri Raden Fatah Palembang, 2018)
This study aims to examine the influence of morning prayers on the formation of student ideal dimensions. The subject of the study was a student of Faculty of Psychology xx in Makassar. This research uses experimental method by including as many as 27 students who have been through the assessment stage. The data collection tool used in this research is the ideal dimension of student dimension (DIM). The data obtained were analyzed using paired samples t test with SPSS for Window program. In the experimental process, students are given group counseling services in the form of virtues and aspects of the morning prayer ruhiyah. The results showed mean DIM before and after the test was significantly different (t (.26) = -1.263, p < 05). Where mean DIM after test is higher (mean = 95.7407) than mean DIM before test. With the results it can be stated that the morning prayer is able to form the ideal dimension of Student. The ideal value of the students that comes from the implementation of the morning prayers is the aspect of IQ (tough and confident in seeking a successful study), EQ (empathy, assertiveness and leadership in social life) and SQ (honest and always maintain religiosity). It is an intrinsically ideal student ideal that is needed in college to support qualified human resources in the future.